2023
DOI: 10.2147/prbm.s396114
|View full text |Cite
|
Sign up to set email alerts
|

Towards Examining the Link Between Green HRM Practices and Employee Green in-Role Behavior: Spiritual Leadership as a Moderator

Abstract: Purpose Grounding on the supplies-values fit theory, this study examines the effect of green HRM practices on an employee’s in-role green behavior after the Covid-19 pandemic. Moreover, this study examined the mediating role of psychological green climate between green HRM practices and in-role green behaviour. In addition, we studied that spiritual leadership as a buffering mechanism strengthens the relation between psychological green climate and employee in-role behavior. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 83 publications
(132 reference statements)
0
11
0
1
Order By: Relevance
“…The study examined the relationship between the use of HR Analytics and organizational performance in a sample of 95 Iranian manufacturing rms. The ndings of the study showed that the use of HR Analytics has a positive effect on organizational performance, which suggests that HR Analytics can contribute to the overall effectiveness of an organization (Li et al, 2023).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 85%
“…The study examined the relationship between the use of HR Analytics and organizational performance in a sample of 95 Iranian manufacturing rms. The ndings of the study showed that the use of HR Analytics has a positive effect on organizational performance, which suggests that HR Analytics can contribute to the overall effectiveness of an organization (Li et al, 2023).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 85%
“… 68 High-quality LMX can bring employees a sense of psychological security and emotional commitment, enhance their sense of belonging and self-efficacy, reduce their worries about uncertainty and risks in the process of active voice, increase their initiative, and thus reduce silent behavior. 69 (4) With the help of bootstrap tests, we found that leader-member exchange mediates the effect of leader self-deprecating humour on silent behaviour and this effect is complete. It means that simply raising the level of self-deprecating humor in leaders does not directly affect employee silence.…”
Section: Discussionmentioning
confidence: 97%
“…In Chinese companies, where hierarchy is well defined and power distance is large, it is not common for employees to openly violate their leaders in the organization. 31 Therefore, in this study, we investigated from the first perspective. Since employee bootlegging plays such an important role for organizations to develop, many scholars begin to explore what factors trigger employees to adopt bootlegging in their daily work.…”
Section: Literature Review and Assumptionsmentioning
confidence: 99%